(untitled) (Proceedings of the International Conference on Public Health, 2022)
Insecticide resistance is a major problem in dengue vector control in Indonesia. Salatiga City, one of Central Java’s dengue-endemic areas, has been using insecticide for vector control for decades. To select the insecticide used, it is necessary to understand the status and mechanism of resistance to various insecticides. This study aimed to determine the status and mechanism of Aedes aegypti resistance in Salatiga City. This study used a descriptive method. Larvae were collected from 8 endemic villages in Salatiga City. The larvae were then reared to produce adult mosquitoes. A resistance test was conducted using the WHO-Impregnated paper method on F1 mosquitoes. The insecticides used for the test were malathion 5%, phenytotrione 1% (Organophosphate); Bendiocarb 0.1%, Propoxur 0.1% (Carbamate); Lambda Cyhalothrin 0.03%, Deltamethrin 0.05%, Permethrin 0.25%, and Cypermethrin 0.05.% (Pyretrhoid). To determine the resistance mechanism of the target site mutation, sequencing of the Domain II VGSC and ACE1 genes was carried out. The test results showed that Ae. aegypti from 8 locations were resistant to all insecticides. The highest mortality after 24 hours observation was on organophosphate group. Molecular tests showed that Single Nucleotide Polymorphism had occurred in the S989P and V1016G alleles of the VGSC gene, indicating molecular resistance to Pyretrhoid insecticides. The ACE1 gene sequences showed no mutations in the G119S allele, indicating the possibility of metabolic resistance to organophosphates and carbamates. In case of a dengue outbreak, it is recommended to use organophosphate because it has the highest percentage of mosquito mortality, and only metabolic resistance occurs without target site mutations.